Effect of Acute and Chronic Electroconvulsive Shock on 5-Hydroxytrypamine 6 Receptor Immunoreactivity in Rat Hippocampus - 김현정; 강승우; 김현주; 최선혜; 신승근; 이형하; 임혜원; 신경호 (한국뇌신경과학회, 2014)
Electroconvulsive shock (ECS) induces not only an antidepressant effect but also adverse effects such as amnesia. Onepotential mechanism underlying both the antidepressant and amnesia effect of ECS may involve the regulation of serotonin(5-hydroxytryptamine) 6 (5-HT6) receptor, but less is known about the effects of acute ECS on the changes in 5-HT6 receptorexpression in the hippocampus. In addition, as regulation of 5-HT receptor expression is influenced by the number of ECS treatmentand by interval between ECS treatment and sacrifice, it is probable that magnitude and time-dependent changes in 5-HT6 receptorexpression could be influenced by repeated ECS exposure. To explore this possibility, we observed and compared the changes of5-HT6 receptor immunoreactivity (5-HT6 IR) in rat hippocampus at 1, 8, 24, or 72 h after the treatment with either a single ECS (acuteECS) or daily ECS for 10 days (chronic ECS). We found that acute ECS increased 5-HT6 IR in the CA1, CA3, and granule cell layerof hippocampus, reaching peak levels at 8 h and returning to basal levels 72 h later. The magnitude and time-dependent changes in5-HT6 IR observed after acute ECS were not affected by chronic ECS. These results demonstrate that both acute and chronic ECStransiently increase the 5-HT6 IR in rat hippocampus, and suggest that the magnitude and time-dependent changes in 5-HT6 IR inthe hippocampus appear not to be influenced by repeated ECS treatment.